Modelling graduate skill transfer from university to the workplace. Issue 2 (17th February 2016) - Jackson, Denise
Abstract : This study explores skill transfer in graduates as they transition from university to the workplace. Graduate employability continues to dominate higher education agendas yet the transfer of acquired skills is often assumed. The study is prompted by documented concern with graduate performance in certain employability skills, and prevalent skill gaps across developed economies. Using confirmatory factor analysis (CFA) and structural equation modelling (SEM), it models skill transfer in 674 business graduates from 39 different Australian universities. Findings support extant literature with the three areas of learner, learning programme and workplace characteristics influencing transfer. The model highlights the need for a more process-oriented, rather than outcomes-focused, approach to the acquisition and transfer of skills in graduates and the shared responsibility of transfer among stakeholder groups. There is a lack of variation among different graduate groups which suggests a generic model of skill transfer and intervention strategies for educators and employers may be implemented as bestpractice. Ultimately, graduate employers will enhance their investment return on new recruits; educators are more likely to achieve goals of work readiness; and individuals will benefit from career progression and intangible rewards associated with improved performance.